(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2023)
The paper examines the causes of Gender-Based Violence (GBV) in Namibia as presented by Namibian women writers in the anthology ‘We Must Choose Life’ (2008). Gender-based violence against women is a worldwide problem and a global concern. Many women globally, Namibian women included, have remained in abusive relationships because of their dependence on the perpetrators of violence for socio-economic support. As explicated by the poems, some Namibian men treat women as the offenders, and the treatment of women at the hands of the men is compared to Apartheid, slavery, and colonialism. It is safe to say that Namibian women are viewed through the lens of the "aristocratic mind," where they are viewed as weak, oppressed and marginalised in their respective societies. The anthology, ‘We Must Choose Life’ (2008), compiled by a Namibian feminist, Elisabeth !Khaxas, breaks the silence of Namibian women and evinces their desire to work towards equality and civilised societies. The paper employs a content analysis approach to analyse the projections of GBV in selected poems and short stories from the anthology. A textual analysis of the creative texts is also undertaken, couched within the theoretical framework of Ecofeminism, which examines the suffering of women from the dominant influence of a male-oriented society. In this respect, specific forms of the abuse of women have been identified as gender-based violence with a level of acceptability. The paper establishes the proliferation in Namibia, of trends in which, some women have endured long-standing abusive relationships because of an over-dependence on the male perpetrators of violence for socio-economic support, fear of the perpetrators’ reprisals, as well as conformity to cultural and religious practices. These narratives bear witness to the bravery of Namibian women to express their anguish and suffering through their own words.